Pelatihan Penerapan Media Sosial Instagram Untuk Memperluas Komunikasi dan Informasi Pada Karang Taruna Tangerang - Syahriani; Sulistianto Sw; Ardian Dwi Praba; tri santoso (CV. Multi Kreasi Media, 2022)
The Ministry of Social Affairs as a supervisor, both functional and technical, always encourages youth groups to always remain productive and work during the COVID-19 pandemic. Various forms of activities have been programmed and carried out by the Rw 23 Youth Organization Organization. In order to suppress the spread of Covid-19, the Rw 23 Youth Organization activists held various social actions in the rw 23 area of ​​Pasar Kemis sub-district, such as the movement to clean the environment and manufacture covid task force. In addition, the youth organizations of RW 23 also carry out activities to educate residents regarding clean and healthy lifestyles as well as distribute basic necessities within the neighborhood of RW 23 residents and many other activities. Although there are many activities that have been carried out by this mass organization, not many people know about the existence of this organization, even though there are only a few people and they do not know for sure what activities this mass organization has carried out and whether this mass organization is very active. active or passive. Therefore, to expand information and communication between this organization and the wider community, it is necessary to have social media assistance such as Instagram, so that the activities carried out and those that have been carried out can be well documented and can make the wider community more acquainted with and increase their trust. to the youth organization rw 23. Because of this, this community service activity was carried out with the aim of helping RW 23 youth organization activists to have a virtual community using Instagram social media so that information or activities of this mass organization can be spread and increasingly known by the wider community.